Determinant Factors Related to the Successful Smooth Delivery Process in the West Aceh District - Yushida Yushida; Cut Nurhasanah; Nurdahliana (Science Midwifery, 2022)
The proportion of deliveries carried out at home and assisted by traditional birth attendants, especially in rural areas, is still high. Most cases of maternal deaths occur in hospitals and are referral cases. These conditions indicate that maternal deaths are due to being late in recognizing danger signs, and being late in taking care decisions is still high. The research focuses on identifying factors related to the smooth delivery process in West Aceh District. This research is an analytic survey using a cross-sectional approach. The research was conducted in West Aceh District. The population in this study were all mothers giving birth in West Aceh Regency in August-September 2021, as many as 94 people. The results showed that the husband's support had a significant relationship with the smooth delivery process in Aceh Barat District (p-value 0.089). Midwife support and maternal readiness are significantly related to the smooth delivery process in Aceh Barat District (P-value 0.001).